Factors controlling carbonate slope failures: Insight from stratigraphic forward modelling - Liu, Jianliang; Liu, Keyu; Salles, Tristan; Li, Changwei (Earth-science reviews, 2022)
A carbonate slope links platform and basin-floor regions holding crucial information on the carbonate source-sink system of a vast ocean. There is a generally poor understanding of the entire process of carbonate slope deposition, failure, and subsequent transportation and redeposition etc. due to the lack of field observation and adequate numerical modelling algorithms. Based on a comprehensive literature review on carbonate slope failures, a three-segment carbonate slope depositional model was conceptualized and simulated using a stratigraphic forward modelling (SFM) program. The model is capable of simulating carbonate slope failures in a) subaerial, b) shallow marine, and c) deep marine settings concurrently. The SFM program was employed to simulate the evolution of carbonate slope and the occurrence and distribution of mass transport deposits (MTDs) in a deeply buried upper Ediacaran carbonate succession in the central Sichuan Basin, China. The simulation results show that MTDs were mainly developed at the toe-of-slopes and in the center of the Ediacaran trough, offering a new potential play for future hydrocarbon exploration in the area. Several key factors controlling carbonate slope failures, including carbonate lithologies, carbonate growth rates, and frequencies and amplitudes of sea-level fluctuations, were quantitatively evaluated in both time and space domains. Simulations have confirmed that carbonate lithologies can notably affect the frequency and magnitude of slope failures and the development of MTDs, indicating that the higher the proportions of coarser and cemented sediments, the less frequent slope failures and the less the volume of the MTDs would be. The frequency of slope failures and the volume of the MTDs would increase with carbonate growth rates. Slope failures are more likely to be triggered by high-frequency sea-level fluctuations than by low-frequency sea-level changes. For a given sea-level change frequency, the magnitude of a single slope failure event and the total volume of associated MTDs are more likely to be more significant under a greenhouse climate, with a relatively smaller amplitude of sea-level changes, than under an icehouse climate.